2014
DOI: 10.1590/s1516-8913201402043
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes: exploitation as a tool in plant protection

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 48 publications
0
61
0
6
Order By: Relevance
“…Endophytes are microorganisms that symbiotically colonized within plant tissues for all or a part of their life cycle without causing any harmful effect to their host (Hirsch and Braun, 1992; Wilson, 1995). Fungal endophytes benefit and offer several advantages to their host by preventing them from desiccation, promoting plant growth hormone, increasing nutrients acquisition, protecting from insect, pathogenic fungi and environmental harsh conditions (Dutta et al, 2014;Nair and Padmavathy, 2014). Meanwhile, the host plant would provide the endophytes with shelters, space for their colonization and also nutrients acquired by them (Saikkonen et al, 2004;Schardl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes are microorganisms that symbiotically colonized within plant tissues for all or a part of their life cycle without causing any harmful effect to their host (Hirsch and Braun, 1992; Wilson, 1995). Fungal endophytes benefit and offer several advantages to their host by preventing them from desiccation, promoting plant growth hormone, increasing nutrients acquisition, protecting from insect, pathogenic fungi and environmental harsh conditions (Dutta et al, 2014;Nair and Padmavathy, 2014). Meanwhile, the host plant would provide the endophytes with shelters, space for their colonization and also nutrients acquired by them (Saikkonen et al, 2004;Schardl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…When tested against different pathogenic bacteria, such as Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli (Ratnaweera et al, 2015) and different fungi and yeasts, including Candida albicans (Premjanu et al, 2016), it demonstrated a strong antimicrobial action. Thus, compounds produced by endophytic fungi of plants with recognized biological activity for biotechnological purposes can be applied in the alternative control of urban and agricultural pests (Dutta et al, 2014), in place of the toxic chemicals sold on the commercial market.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes are the group of microorganisms that live inside host microenvironment, receive protection from environmental stresses, face lesser competition from other microbes and have greater access to nutrients [1]. Since endophytes interact closer to plant than rhizosphere and phyllosphere bacteria, their effects to the plants may be direct and intense.…”
Section: Introductionmentioning
confidence: 99%